Aquarium Setup and Maintainence - Ruth Francis-Floyd; Allen Riggs; Roy Yanong (EDIS)
An aquarium can be defined as a container that holds water and is designed in such a way that living aquatic organisms can be maintained over an extended period of time. Aquariums vary tremendously in size and design. They can be as simple as a betta bowl or as complex as a multi-million gallon commercial exhibit. When considering an aquarium it is important to contemplate where it will be located, which species will be maintained and what type of budget will be available. In general, larger aquariums are easier to work with than smaller ones. Greater investment is required, however, and a greater allocation of space is also needed. This document is VM144, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2003.